Bernal Díaz del Castillo: memoria, invención y olvido - Martínez Martínez, María del Carmen, 1962- (2018)
Este artículo da a conocer documentos inéditos que esclarecen el debate abierto sobre Bernal Díaz del Castillo. Se demuestra su capacidad para escribir e incluso su actuación como «escribano». Se recogen testimonios de contemporáneos que le atribuyen la autoría de la Historia verdadera. Se recupera el pleito con el fiscal Villalobos, en el que se conservan tres peticiones del conquistador, y la probanza ad perpetuam rei memoriam que hizo en la villa del Espíritu Santo en marzo de 1539, en la que no consta su participación en la expedición de Grijalva.
This article refers to previously unpublished documents to demonstrate Bernal Díaz de Castillo’s writing skills and role as escribano, to shed light on the open debate surrounding this historical figure. These documents include: testimonies by his contemporaries that accredit him with authorship of Historia Verdadera; the lawsuit of fiscal Villalobos, in which three of the Conquistador’s petitions are conserved; and Probanza ad Perpetuam Rei Memoriam, written in the town of Espíritu Santo in March, 1539, in which there is no mention of his participation in the expedition of Grijalva.
Keywords: Díaz del Castillo, Bernal, -- ca. 1496-1584; Conquistadores